PENGARUH QUALITY OF WORK LIFE (QWL) DAN ORGANIZATIONAL CLIMATE TERHADAP KEPUASAN KERJA YANG BERIMPLIKASI PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) KARYAWAN DI POLITEKNIK LP3I JAKARTA - Ardila, Wahyu; Hulmansyah, Hulmansyah; Huda, Nurul (JURNAL LENTERA BISNIS, 2018)
ABSTRACTThis research has a purpose to find out: the effect of Quality of Work Life (QWL) on Job Satisfaction in LP3I Polytechnic Jakarta; the effect of Organizational Climate on Job Satisfaction in LP3I Polytechnic Jakarta; the effect of Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; the effect of Organizational Climate on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; the effect Job Satisfaction on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta. Data analysis method used is Structural Equation Model (SEM) by using Amos software. Respondents in this study were employees of the Polytechnic LP3I Jakarta totaling 201 samples using the technique of making samplel Probability sampling.The results of this study indicate that there is a positive and significant effect of Quality of Work Life (QWL) on Job Satisfaction in LP3I Polytechnic Jakarta; there is a positive and significant effect Organizational Climate on Job Satisfaction in LP3I Polytechnic Jakarta; there is a positive and significant effect of Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; there is a positive and significant effect Organizational Climate on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; there is a positive and significant effect Job Satisfaction on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta.Keywords: Quality Of Work Life, Organizational Climate, Job Satisfaction and OCB